2015
DOI: 10.1111/apt.13458
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the current treatment of non‐cardiac chest pain

Abstract: SUMMARY BackgroundNon-cardiac chest pain is one of the most common functional gastrointestinal disorders. By recognising that gastro-oesophageal reflux disease (GERD), oesophageal dysmotility and oesophageal hypersensitivity are the main underlying mechanisms of NCCP, a more directed therapeutic approach has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 70 publications
(185 reference statements)
1
30
0
5
Order By: Relevance
“…Trials of empiric proton pump inhibitors have been recommended for concurrent diagnosis and treatment of GERD in patients with chest pain inconsistent with cardiac disease, 25,7578 as GERD is a significant contributor in many cases. 78 From a psychopharma-cological standpoint, a recent meta-analysis of trials evaluating selective serotonin reuptake inhibitors (SSRIs) for the treatment of NCCP concluded that SSRIs were not superior to a placebo in improving symptoms of chest pain, suggesting that psychopharmacology alone is unlikely to be a sufficient management approach for NCCP. 79 Notably, 3 of 4 studies included in the meta-analysis excluded patients with comorbid psychiatric disease; as a result, this meta-analysis does not speak to the efficacy of SSRIs in patients with NCCP who have comorbid SSRI-responsive psychiatric conditions (e.g., MDD).…”
Section: Interventions To Treat Nccpmentioning
confidence: 99%
“…Trials of empiric proton pump inhibitors have been recommended for concurrent diagnosis and treatment of GERD in patients with chest pain inconsistent with cardiac disease, 25,7578 as GERD is a significant contributor in many cases. 78 From a psychopharma-cological standpoint, a recent meta-analysis of trials evaluating selective serotonin reuptake inhibitors (SSRIs) for the treatment of NCCP concluded that SSRIs were not superior to a placebo in improving symptoms of chest pain, suggesting that psychopharmacology alone is unlikely to be a sufficient management approach for NCCP. 79 Notably, 3 of 4 studies included in the meta-analysis excluded patients with comorbid psychiatric disease; as a result, this meta-analysis does not speak to the efficacy of SSRIs in patients with NCCP who have comorbid SSRI-responsive psychiatric conditions (e.g., MDD).…”
Section: Interventions To Treat Nccpmentioning
confidence: 99%
“…However, treatment options and therapeutic results in patients with NCCP and hypercontractile esophageal motility disorders remain disappointing so far. Medical treatment, endoscopic pneumatic dilation of cardia or tubular esophagus, injection of botulinum toxin into the lower esophageal sphincter or esophageal body, and laparoscopic cardiomyotomy are of limited effect [6]. In this line, surgical myotomy is limited by the required combined abdominal and thoracic approach to reach all hypercontractile segments of the tubular esophagus sufficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with NCCP might be referred to antireflux surgery after ruling out oesophageal motility disorders such as hypercontractile oesophagus and functional chest pain. 39 Although literature on GORD-related NCCP as the sole indication for surgical treatment is non-existent, fundoplication has been performed in this patient group. Improvement after surgical treatment is better in patients with a clear correlation between reflux events and symptoms, in patients who also display typical reflux symptoms such as heartburn and third when there is a satisfactory response to PPIs prior to the surgery.…”
Section: Clinical Presentation and Comorbiditiesmentioning
confidence: 99%